PEMANFAATAN TEMA ARSITEKTUR TRADISIONAL LOKAL TERHADAP TRANSFORMASI BENTUK DAN FUNGSI ARSITEKTUR DI PERKOTAAN DALAM KONTEKS KEKINIAN - Dwiasta R, A Yusdy (Universitas Negeri Makassar, 2014)
Local traditional architecture assessment this time has undergone a change and a shift from age to age. This is due to the emergence of a variety of information and developments in the field of construction that caused the value of traditional architecture eroded and forgotten characters. Utilization of local traditional architectural themes conducted in this paper is to get an overview assessment of the architecture that happens in the present to aspects of form and function continue to be exploited and used in architecture occurring in Urban. Keywords : traditional, architecture, overview assessment